Lip-Nose Reconstruction Post-Cancrum Oris Defect: A Case Report - Sobhan Mishra1 , Shelly Mishra1 , Shibasis Biswas1, Pankaj Kumar Panda1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Cancrumoris is a disease of great antiquity described by Hippocrates and Galen. The termnoma, a commonsynonym for the disease, is derived from the Greek verb ‘to devour’.Tourdes(1948) definedcancrumoris thatis still substantially correct. Hedescribed the condition as a gangrenous affection of the mouth that especiallyattacks children in whom the constitution is altered by bad hygiene and serious illnesses such asexanthematousfevers. According to him, the disease is manifested by an ulcer of the oralmucous membrane, edema of theface extending from within out, and rapid destruction of the soft tissues and bone with an outcome that isalmost always fatal. Nowadays, cancrumoris still affects children predominantly. It occurs very rarely in theaged with decreased hostresistance. Noma sequelae comprise bony and soft-tissue losses that affect bothaesthetics and function. Complex defects should be treated in a staged fashion with the most complex initialstages performed in better-equipped institutions and less complex stages done on home ground. Althoughcomplete correction may be planned to restore function and aesthetics, thenoma patient may eventually besatisfied with a functional but less aesthetic outcome.